Investigating an English Teacher’s Cognitive and Metacognitive Behavior: Thinking Aloud Protocols Analysis - Helena Verusha Ali; Bayu Andika Prasatyo (Jurnal Pendidikan Bahasa, 2023)
This study seeks to demonstrate the importance of clarity and accuracy in post-editing activity, From the perspective of metacognitive and cognitive processes proposed by Wenden' (1991).The research design of this study is a qualitative design. The data were two different translated texts. The post-editing activity was conducted online via Zoom meeting. This article uncovered that there are three types of cognitive and three types of metacognitive strategies implemented by the post-editor. ). Further, the findings also show that the post-editor’s metacognitive strategies include planning (i.e., reconsidering written text), monitoring (i.e., checking and verifying the text), and evaluating (i.e., revising the text.